Comparison of Tooth Color and Enamel and Dentinal Thickness between Orthodontically Treated and Untreated Individuals - Hakami, Zaki; Marghalani, Hussain YA; Hedad, Ismaeel; Khawaji, Mazen; Abutaleb, Ghadah; Hakami, Amjad; Almoammar, Salem; Alshehri, Abdulrahman (Diagnostics (Basel), 2023)
This study compared tooth color and enamel and dentinal thickness between orthodontically treated and untreated individuals. (1) Methods: A matched case–control study was conducted. The sample included 26 patients who had received orthodontic treatment and 31 matched controls. The color assessment was performed subjectively using the VITA 3D-Master (VM) shade guide and objectively using the VITA Easyshade (VE) spectrophotometer. Differences in L*, a*, and b* (lightness, red/green, and blue/yellow) were calculated. The color change was evaluated using ΔE*ab and the whiteness index (WID). Tooth structure thickness (labiolingual, labial enamel, and labial dentin) was evaluated using cone-beam computerized tomography. The correlations between overall tooth color and tooth structure thickness were evaluated. (2) Results: A total of 228 teeth were evaluated. Color assessment using VM showed significant differences between orthodontically treated and untreated teeth (p < 0.001), while VE revealed no significant differences. Both groups showed no difference in tooth enamel and dentinal thickness. Significant differences in tooth color (p < 0.05) were observed between genders. Both VM and VE showed weak to moderate correlations with tooth color and enamel and dentinal thickness (p < 0.05). (3) Conclusions: Orthodontic treatment may demonstrate visually perceptible but acceptable and clinically undetectable tooth color alteration.